The antidepressant effects and serum metabonomics of bifid triple viable capsule in a rat model of chronic unpredictable mild stress - Bu, Qinpeng; Zhang, Jingkai; Guo, Xiang; Feng, Yifei; Yan, Huan; Cheng, Weimin; Feng, Zhitao; Cao, Meiqun (Frontiers in Nutrition, 2022)
Background Probiotics have shown potential antidepressant effects. This study evaluated the effect and probable mechanisms of bifid triple viable capsules (BTVCs) on a rat model of chronic unpredictable mild stress (CUMS). Methods Rats were randomly divided into Normal, CUMS model, FLX, BTVCs, and FLX+BTVCs groups. Depressive-like behaviours, pathological changes in the hippocampus, changes in serum metabolites and potential biomarkers, and metabolic pathways were detected via behavioural tests, haematoxylin-eosin staining, Nissl staining, nontargeted metabolomics, and ingenuity pathway analysis (IPA). Results The rats displayed depressive-like behaviours after CUMS exposure, but BTVCs ameliorated the depressive-like behaviours. In addition, the pathological results showed that the hippocampal tissue was damaged in rats after CUMS exposure and that the damage was effectively alleviated by treatment with BTVCs. A total of 20 potential biomarkers were identified. Treatment with BTVCs regulated D-phenylalanine, methoxyeugenol, (±)-myristoylcarnitine, 18:3(6Z,9Z,12Z) /P-18:1(11Z), propionyl-L-carnitine, and arachidonic acid concentrations, all compounds that are involved with glycosylphosphatidylinositol-anchor biosynthesis, glycerophospholipid metabolism or the arachidonic acid metabolism pathway. The IPA demonstrated that endothelin-1 signaling and cyclic adenosine monophosphate response element binding protein (CREB) signalling in neurons may be involved in the development of depression. Conclusion Our findings suggest that BTVCs can alleviate depressive-like behaviours, restore damage to the hippocampus in CUMS rats and regulate serum metabolism, which may be related to endothelin-1 signaling or CREB signaling in neurons.